Granuloma annulare and necrobiosis lipoidica with sequential occurrence in a patient: report and review of literature - Katherine A. Rupley; Ryan R. Riahi; Deirdre O'Boyle Hooper (Mattioli1885, 2015)
Granuloma annulare (GA) and necrobiosis lipoidica (NL) are granulomatous diseases of undetermined etiology. Rarely, both dermatoses have been reported to occur concomitantly in patients. GA and NL are characterized histologically by areas of necrobiosis of collagen. The two diseases share some common characteristics, which may suggest that these dermatoses could occur as a spectrum in some patients or possibly share a similar pathogenesis. We report on a 67-year-old Caucasian woman with a history of NL on the anterior shins that later developed lesions of GA on the breasts, trunk, and wrist. We also review the literature and discuss the characteristics of patients with concomitant GA and NL.